2004
DOI: 10.1080/14639230400005990
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cost and assessment of computerized patient record systems in Japan based on questionnaire survey

Abstract: Our findings indicate that the maker of CPR system, number of servers, institution type and implementation date had a strong influence on per-bed implementation costs in that order. Finally, it was found that CPR systems were considered effective for hospital administration and medical examinations, based on the high assessments of the results of installing a CPR system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…17–57 Twelve papers focused on costs and impacts, that is, costs and benefits or cost-effectiveness 2223 30 32 33 38 39 41 42 47 51 55 Twelve papers were on system costs,4 17–19 26 27 34 37 40 45 53 56 while 12 others examined the impact of systems on costs 2024 25 29 31 35 36 44 48 50 52 57 Six papers looked at cost savings 21…”
Section: Resultsmentioning
confidence: 99%
“…17–57 Twelve papers focused on costs and impacts, that is, costs and benefits or cost-effectiveness 2223 30 32 33 38 39 41 42 47 51 55 Twelve papers were on system costs,4 17–19 26 27 34 37 40 45 53 56 while 12 others examined the impact of systems on costs 2024 25 29 31 35 36 44 48 50 52 57 Six papers looked at cost savings 21…”
Section: Resultsmentioning
confidence: 99%
“…Previous research shown, however, that IT is used for different aims in different organizations, [2,5,10,11,20,25,34,38,48,49,51,65,95,117,118,121,123,131,144,145] consequently, it is rational to expect that in order to capture where the values of IT-innovations come from it is necessary to first identify the context in which IT is implemented. For this reason, when building the contexts' landscape in this study, we used the principle of coherence [11] and tried to reflect these organizational contextual differences by theoretically classifying the contexts in which an IT-innovation is applied into three types:…”
Section: Methodsmentioning
confidence: 99%